2021
DOI: 10.1002/int.22386
|View full text |Cite
|
Sign up to set email alerts
|

Organic solar cells defects classification by using a new feature extraction algorithm and an EBNN with an innovative pruning algorithm

Abstract: Physical defects reduce the organic solar cells (OSC) functioning. Throughout the OSC fabrication process, the defects can occur, for instance, by scratches or uneven morphologies. In general, bulk defects, interface defects, and interconnect defects can promote shunt and series resistance of the cell. It is crucial to properly detect and classify such defects and their amount in the structure. Correlating such defects with the performance of the cell is important both during the R&D stages to optimize process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Anomalies in connection with criminal activity are the focus of future work wherein a deep learning neural network can be used as a classifier to investigate them. Furthermore, similar applications of machine learning can be explored in different fields [31], such as classifying the defect in organic cells and many more. Similarly, work can be extended to detect the malfunction of solar tracking systems and normal function, referring to [32].…”
Section: Discussionmentioning
confidence: 99%
“…Anomalies in connection with criminal activity are the focus of future work wherein a deep learning neural network can be used as a classifier to investigate them. Furthermore, similar applications of machine learning can be explored in different fields [31], such as classifying the defect in organic cells and many more. Similarly, work can be extended to detect the malfunction of solar tracking systems and normal function, referring to [32].…”
Section: Discussionmentioning
confidence: 99%
“…They handle every input individually using separate weights. Sciuto et al [4], [22] use elliptical basis neural networks for detecting defects in organic solar cells.…”
Section: Related Workmentioning
confidence: 99%
“…However, the device stability was rather poor due to the rapid dissolving of the perovskite materials in organic solvents. Subsequent explorations by many scientists have led to numerous improvements in aspects such as perovskite materials and device structures, thus pushing the research and enthusiasm related to PSCs to a higher level [ 15 , 16 , 17 ]. Among them, one of the most promising route is go all-inorganic, as extensive researches have shown that all-inorganic halide perovskites express superior intrinsic structural stability and much lower sensitivity against humidity environment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%